Using implementation mapping for the adoption and implementation of Target:BP in community health centers - Valerio-Shewmaker, Melissa A.; Heredia, Natalia I.; Pulicken, Catherine; Mathews, Patenne D.; Chenier, Roshanda; Swoboda, Tracy L.; Garza, Ella R.; Velasco-Huerta, Fernanda; Fernandez, Maria E. (Frontiers in Public Health, 2022)
Despite the availability of multilevel evidence-based interventions for blood pressure management, poor hypertension control is common among community health center patient populations across the state of Texas and the United States. Target:BP is a national initiative from the American Heart Association and the American Medical Association to assist healthcare organizations and care teams in improving blood pressure control using evidence-based approaches and recognition of organizations who have successfully integrated the program in practice. Using the Implementation Mapping (IM) approach, we identified determinants of Target:BP adoption and use and developed strategies to improve program uptake and implementation in Community Health Centers (CHC) in Texas. We used IM to identify barriers and facilitators influencing the adoption and implementation of Target:BP program and develop strategies to increase program adoption and use. We recruited four clinics across four counties in Texas and assessed barriers and facilitators at the organizational level, including electronic health records and data use. We used this data to inform clinic-specific implementation strategies based on the organization capacity and priorities feedback to improve the implementation and maintenance of Target:BP. As part of the needs and capacity assessment, we collected data through interviews with CHC staff, examining gaps in needs and services (e.g., what do clinics need to implement Target:BP), and assets to leverage. We worked with CHCs to a) identify individuals who would be involved in the adoption, implementation, and maintenance of Target:BP; b) describe adoption and implementation actions, and c) identify barriers and facilitators influencing adoption and implementation. We used IM approach to identify and develop program goals, identify methods and strategies to address barriers, and create an implementation plan. We developed a Target:BP implementation protocol for each clinic based on the needs and capacity assessment, identification of technology use and capacity, and gap analysis. Ongoing process and impact evaluations using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework are underway. This paper provides an example of using Implementation Mapping to develop strategies to increase the adoption and implementation of evidence-based cardiovascular risk reduction interventions in CHCs to increase the use of Target:BP in CHCs to improve hypertension control.